Is it possible to predict the blood volume of a sick preterm infant?. Issue 4 (21st June 2004) - Aladangady, N; Aitchison, T C; Beckett, C; Holland, B M; Kyle, B M; Wardrop, C A J
Abstract : Objective: To investigate the relation between the measured intravascular blood volume (BV) and current methods of indirectly assessing BV status in sick preterm infants on the first day of life. Methods: Thirty eight preterm infants of gestation 24–32 weeks (median 30) and weight 480–2060 g (median 1220) were studied. Red cell volume was measured by the fetal haemoglobin dilution method in six infants and by the biotin labelled autologous red cell dilution method in the remaining 32. Total BV was calculated by dividing red cell volume by packed cell volume. Indirect assessments of BV status using heart rate (HR), core-peripheral temperature difference, mean arterial pressure, base excess, and packed cell volume were recorded. Results: The mean (SD) initial measured BV was 71 (12) ml/kg (range 53–105). The mean HR was 148 beats/min (range 130–180), which correlated positively ( r   =  0.39, p  =  0.02) with BV (higher HR was associated with higher BV). The mean base excess was −3.19 mmol/l (range −18 to +6.2). The negative base excess correlated significantly positively ( r   =  0.41, p < 0.01) with BV (more acidotic babies tended to have higher BV). There was no significant correlation between core-peripheral temperature difference, mean arterial pressure, or packed cell volume and BV. Regression analysis showed that base excess and HR were significantly related to BV; base excess alone can predict variability in BV only to17%, and base excess with HR can predict variability in BV to 29%. Conclusion: The conventional clinical and laboratory indices are poor predictors of measured blood volume.